COL4A1 gene mutation – beyond a vascular syndrome. (September 2015) - John, Seby; Jehi, Lara; Manno, Edward M.; Conway, Devon S.; Uchino, Ken
Highlights: COL4A1 affect vascular basement membrane in multiple organs systems. In children congenital porencephaly or intracerebral hemorrhage, and infantile hemiparesis can result. In adults mental retardation, migraine, seizure, stroke and intracerebral hemorrhage are reported. Seizures are part of the clinical spectrum of COL4A1 mutation. Seizures in COL4A disorder may not be solely due to vascular compromise. COL4A1 mutation may alter the threshold potentials for seizure generation.